Levodopa and Plant-Derived Bioactive Compounds in Parkinson's Disease: Mechanisms, Efficacy, and Future Perspectives - Aktas, Emre; Hanagasi, Hasmet Ayhan; Ozgenturk, Nehir Ozdemir (WILEY, 2025)
Background: Parkinson's disease (PD) is a progressive neurodegenerative disorder characterized by the degeneration of dopaminergic neurons in the substantia nigra, resulting in dopamine deficiency and motor dysfunction. While levodopa (L-DOPA) remains the gold standard for symptomatic treatment, its long-term administration is associated with complications such as motor fluctuations, dyskinesia, and oxidative stress. Given these limitations, interest has grown in plant-derived bioactive compounds for their potential neuroprotective and disease-modifying effects. Methods: A systematic literature review was conducted across PubMed, Scopus, Google Scholar, and Web of Science, focusing on peer-reviewed studies published between 2023 and March 2025. The inclusion criteria targeted in vitro and in vivo preclinical studies as well as clinical trials that directly compared levodopa with plant-derived compounds in the context of PD. Key search terms included Parkinson's disease, levodopa, phytochemicals, and plant-based neuroprotection. Results: Recent studies have highlighted several classes of plant-based compounds-including polyphenols (resveratrol, curcumin, EGCG), flavonoids (quercetin, apigenin, naringenin), alkaloids (berberine, caffeine, L-DOPA derived from Mucuna pruriens), and terpenoids (ginkgolide B, celastrol)-as potential neuroprotective agents. These compounds exert multiple actions, such as reducing oxidative stress, blocking neuroinflammation, preventing alpha-synuclein aggregation, and protecting mitochondria. Although levodopa effectively addresses motor symptoms, these phytochemicals may complement conventional therapy by targeting underlying disease processes. Conclusions: Although levodopa is indispensable for the symptomatic management of PD, emerging evidence supports the integration of plant-derived bioactive compounds as adjunct therapies with disease-modifying potential. Future research should prioritize improving bioavailability, developing standardized formulations, and conducting long-term clinical trials to evaluate the translational applicability of these natural agents in Parkinson's disease therapy.
Keywords: levodopa and motor fluctuations; oxidative stress and neuroinflammation in PD; Parkinson's disease therapy; phytochemicals as adjuncts in PD treatment; plant-derived bioactive compounds in Parkinson's disease; plant-derived neuroprotective compounds; OXIDATIVE STRESS; MUCUNA-PRURIENS; MODULATION; PATHWAY; Neurosciences & Neurology; Pharmacology & Pharmacy